Obesity, body height and risk of venous thromboembolism - Horvei, Lars Daae (UiT The Arctic University of Norway, 2018)
The papers I and IV of this thesis are not available in Munin. Paper I: Horvei, L. D., Brækkan, S. K., Mathiesen, E. B., Njølstad, I., Wilgaard, T., Hansen J. B.: «Obesity measures and risk of myocardial infarction and venous thromboembolism”. Available in Eur J Epidemiol. 2014 Nov; 29(11): 821-30. Paper IV: Horvei, L. D., Brækkan, S. K., Smith, E. N., Solomon, T., Hindberg, K., Frazer, K. A., Rosendaal, F. R., Hansen, J. B.: “Joint effects of prothrombotic genotypes and body height on the risk of venous thromboembolism: The Tromsø Study”. (Manuscript). Published version available in J Thromb Haemost 2018; 16: 83–9. Venous thromboembolism (VTE) is a collective term for deep vein thrombosis (DVT) and pulmonary embolism (PE). Obesity, as well as a tall stature, are well-known and substantial risk factors for VTE, but the underlying mechanisms behind these associations are not fully understood. The aims of this thesis were to investigate how different patterns of body fat distribution, levels of obesity-related cardiovascular risk factors and chronic, low-grade inflammation influenced the risk of venous and arterial thrombosis. Further, we wanted to investigate whether changes in body weight over time was associated with VTE risk. Finally, we sought to explore if the combined presence of a tall stature and genetic pro-thrombotic risk factors yielded synergistic effects on the risk of VTE. The study populations in this thesis were recruited from the third (1986-87) through the sixth (2007-2008) surveys of the Tromsø study, a large population-based cohort. Exposure information was obtained through self-administered questionnaires, blood samples and physical examination. Incident VTE events during follow-up were registered and thoroughly validated. In the first paper, we found that body fat distribution had a differential impact on venous and arterial thrombosis, where subjects with wide hips were at elevated risk of VTE but not MI. Further, cardiometabolic abnormalities such as insulin resistance, hypertension and ...